Extended Nicotine Patch Treatment Among Smokers With and Without Comorbid Psychopathology. Issue 1 (12th September 2018) - Carroll, Allison J; Mathew, Amanda R; Leone, Frank T; Wileyto, E Paul; Miele, Andrew; Schnoll, Robert A; Hitsman, Brian
Abstract: Introduction: Individuals with psychiatric conditions smoke at higher rates than the general population and may need more intensive treatment to quit. We examined whether or not extended treatment with nicotine patch, combined with behavior counseling, would disproportionally benefit smokers with versus without a lifetime psychiatric condition. Methods: We conducted a secondary analysis of data from an effectiveness trial of treatment with 12 counseling sessions (48 weeks) and 21-mg nicotine patch (8, 24, or 52 weeks) among 525 adult daily smokers. A structured clinical interview assessed past and current psychiatric disorders (major depression, generalized anxiety disorder, alcohol abuse and/or dependence, and substance abuse and/or dependence), as described in the Diagnostic and Statistical Manual of Mental Disorders (Fourth Edition). Abstinence was bioverified at week 52. Logistic regression evaluated the effect of the psychiatric status × treatment duration interaction on abstinence at week 52, covarying for sociodemographics, baseline psychological symptoms, and treatment adherence. Results: At baseline, 115 (21.9%) participants were diagnosed with one or more psychiatric conditions. The psychiatric status × treatment duration interaction was significant for week 52 abstinence ( p = .027). Abstinence rates between smokers with versus without a psychiatric condition in the 24-week treatment arm (9.3% vs. 31.5% abstinent) significantly differed from the 8-week treatment arm (18.8% vs. 22.3%), p = .017. Abstinence rates for smokers with (22.5%) versus without a psychiatric condition (19.7%) in the 52-week treatment arm did not differ from those in the 8-week arm. Conclusions: Targeted smoking cessation treatment, rather than extending treatment duration, may be especially warranted to optimize treatment for smokers with comorbid mood, anxiety, and substance use disorders. Implications: Individuals with psychiatric conditions smoke at higher rates and have greater difficulty quitting compared to those in the general population, but little is known about how to best optimize treatment for this high tobacco burden population. The present study found that cessation response to extended duration treatment with the transdermal nicotine patch did not differ for smokers with versus without comorbid anxiety, mood, and substance use disorders in a large-scale clinical effectiveness trial. Development of targeted behavioral treatments may be required to optimize abstinence outcomes for this high-risk population, rather than simply extending the duration of pharmacotherapy treatments.